Pembrolizumab monotherapy for previously untreated, PD-L1-positive, metastatic triple-negative breast cancer: cohort B of the phase II KEYNOTE-086 study. (26th November 2018) - Adams, S; Loi, S; Toppmeyer, D; Cescon, D W; De Laurentiis, M; Nanda, R; Winer, E P; Mukai, H; Tamura, K; Armstrong, A; Liu, M C; Iwata, H; et al.
Abstract: Background: Standard first-line treatment of metastatic triple-negative breast cancer (mTNBC) is chemotherapy. However, outcomes are poor, and new treatment options are needed. In cohort B of the phase II KEYNOTE-086 study, we evaluated pembrolizumab as first-line therapy for patients with PD-L1-positive mTNBC. Patients and methods: Eligible patients had centrally confirmed mTNBC, no prior systemic anticancer therapy for metastatic disease, measurable disease at baseline per RECIST v1.1 by central review, no radiographic evidence of central nervous system metastases, and a tumor PD-L1 combined positive score ≥1. Patients received pembrolizumab 200 mg intravenously every 3 weeks for up to 2 years. The primary end point was safety. Secondary end points included objective response rate, disease control rate (percentage of patients with complete or partial response or stable disease for ≥24 weeks), duration of response, progression-free survival and overall survival. Results: All 84 patients enrolled were women, and 73 (86.9%) received prior (neo)adjuvant therapy. Fifty-three (63.1%) patients had treatment-related adverse events (AEs), including 8 patients (9.5%) with grade 3 severity; no patients experienced grade 4 AEs or died because of treatment-related AEs. Four patients had a complete response and 14 had a partial response, for an objective response rate of 21.4% (95% CI 13.9–31.4). Of the 13 patients with stable disease, 2 had stable disease lasting ≥24 weeks, for a disease control rate of 23.8% (95% CI 15.9–34.0). At data cut-off, 8 of 18 (44.4%) responses were ongoing, and median duration of response was 10.4 months (range 4.2 to 19.2+). Median progression-free survival was 2.1 months (95% CI 2.0–2.2), and median overall survival was 18.0 months (95% CI 12.9–23.0). Conclusions: Pembrolizumab monotherapy had a manageable safety profile and showed durable antitumor activity as first-line therapy for patients with PD-L1-positive mTNBC. Clinical trial registration: ClinicalTrials.gov, NCT02447003.